PERAN KEPEMIMPINAN PENDIDIKAN DALAM SISTEM MANAJEMEN KEARSIPAN UNTUK MENINGKATKAN EFISIENSI DAN KEAMANAN DATA DI ERA DIGITAL - Atin Syarifatul Fuadiyah; Aulia Lutfianti; Nazarudin Umar; Zalfa Nur Azizah; Siswadi (STKIP Subang, 2026)
This study aims to examine the role of educational leadership in archival management systems to improve data efficiency and security in the digital era. The development of information technology requires educational institutions to transform archival management from conventional systems to more effective, efficient, and secure digital systems. However, the implementation of such systems cannot be separated from the strategic role of leadership in formulating policies, managing resources, and ensuring system sustainability. This study employs a qualitative approach using a literature review method by analyzing relevant scientific sources. The results indicate that educational leadership plays a crucial role in enhancing efficiency through digital archiving, standardizing procedures, and utilizing information technology. Furthermore, data security is strengthened through data protection policies, access control, and improving digital literacy among educational staff. Therefore, visionary, adaptive, and innovative leadership is essential in optimizing archival management systems in the digital era. Keywords: educational leadership, archival management, efficiency, data security, digital era